Prevalence and Causes of Ulnar Neuropathy in the Electrodiagnosis Clinic of Shohada-e-Tajrish Medical Center - Rayegani, Seyed Mansoor; Nouri, Farshad; Benam, Milad (Archives of Men’s Health, 2021)
Background: The prevalence of ulnar nerve mono neuropathy has increased in recent years. Upper limb involvement by ulnar neuropathy results in motor and sensory disability and this disability imposes significant physical, psychological and financial burdens on patients. We aimed to assess the prevalence and causes of ulnar neuropathy in the Electrodiagnosis clinic of Shohada-e-Tajrish medical center. Materials and Methods: In this cross-sectional study we extracted the electronic files of all patients referred to the clinic during 2009-2013. Patients with ulnar neuropathies were selected and required data were obtained. 62 patients with ulnar nerve lesions were included and their data (include age, sex, involved side, cause of lesion, severity and location of involvement) were analyzed. Results: Of the 62 patients enrolled, 42(67.7%) were men and 20 (32.3%) were women with a mean age of 41.63 years (range: 17-79 years). There was a significant relationship between age and disease prevalence. The highest prevalence rate of the disease was observed in the 20–39year-old age group and the lowest in the below 20-year-old age group. Trauma was a more frequent cause than entrapment. Elbow was the most frequent location of injury. Conclusion:Ulnar neuropathy was more prevalent in young and middle-aged individuals than those above 60 years. Considering the potential disability caused by this nerve damage, more attention is needed to evaluate patients and initiate proper treatment and rehabilitation in those ulnar nerve lesion.